Extracts of Cryopreserved Fragments of Pig Spleen and Piglet Skin Affect the Healing of Cold Wounds in Rats - Bespalova, Iryna G.; Rogoza, Liliya A.; Galchenko, Sergij Ye.; Sandomyrsky, Borys P. (Problems of Cryobiology and Cryomedicine, 2015)
The optimizing of cold wound treatment has been currently remained a relevant task, which can be particularly solved through the introduction of the combined therapy with immune biological products. The experimental animals were injected with 1 ml extract of cryopreserved fragments of either newborn piglet skin or pig spleen into abdominal cavity once a day within the course of experiment. The dose of peptides was 50 Âµg per 100 g of an animal. The control rats were injected with 1 ml of physiological saline once a day. It has been established that introduction to the animals with cold trauma of the extract of cryopreserved fragments of either newborn piglet skin or pig spleen accelerates the healing of cold wounds. Starting from day 7 the area of wounds in the animals, which were injected with the extract of cryopreserved fragments of either newborn piglet skin or pig spleen was statistically and significantly lower than in the control rats. In addition, in the experimental animals the index of blood leukocytes shift was more rapidly normalized. After introduction of the extracts to the animals with cold trauma the rate of free radical oxidation of lipids and the TBARS level in blood serum of the animals with cold injury were reduced. Thus, to day 14 of the experiment in the groups with introduced extract of cryopreserved fragments of either pig spleen or newborn piglet skin the level of TBARS was normalized, and in the control group this happened only to day 21. In the animals introduced with the extracts, the ligand-loading of albumin decreased faster than in the control animals. Probl Cryobiol Cryomed 2015; 25(2): 151-161.